Lecturers' Perceptions of Constructive Critical Thinking Learning in Academic Writing Courses (A Case Study at Makassar State University): Penelitian - Muhammad Tahir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigated lecturers' perceptions and implementation of the Constructive Critical Thinking Learning (CCTL) model in academic writing courses at Makassar State University. The study's introduction highlighted the growing emphasis on critical thinking in Indonesian higher education and the challenges EFL students face in developing academic writing skills. The research aimed to explore lecturers' attitudes towards CCTL, identify perceived benefits and drawbacks, and offer recommendations for improved implementation. Employing an exploratory sequential mixed-methods design, the study collected qualitative data through classroom observations, semi-structured interviews with lecturers and students, and document analysis. Results revealed generally positive lecturer perceptions of CCTL's effectiveness in fostering critical thinking, but also highlighted challenges such as time constraints and the need for more training and institutional support. Variations in CCTL implementation were observed, with some lecturers effectively integrating CCTL strategies while others relied on more traditional methods. The study concludes that while CCTL shows promise, its successful implementation requires addressing practical limitations through professional development and institutional support.